A model for characterizing knowledge utilization in verifying successful knowledge transfer - Abdullah, Salfarina; Hamdan, Hazlina; A. Jabar, Marzanah; Anuar, Sazly (School of Computing, College of Arts and Sciences, Universiti Utara Malaysia, 2018)
Software architecture development is a creative process that requires integration of different knowledge expertise and functionalities hence, open up wide opportunities for those involved to learn from each other. Nevertheless, many assertions have been made about the flow of knowledge transfer being unclear and abstruse therefore led to failure in maximizing knowledge transfer benefits. We respond to this assertions by proposing a model for characterizing the utilization of knowledge in order to verify the occurrence of successful knowledge transfer. The model is derived based on PKAMI, a strategy we invented that comprises of 5 key steps. We further presented a simple case study to show our implementation of the model proposed. The significance of this research is that the model will be able to assist all software practitioners to verify their engagement in knowledge transfer as well as to better strategize on improving and keep on producing quality software project deliverables. We are also aiming at elevating the essence of knowledge utilization by encouraging those involved in development to find ways and opportunities to learn from others’ experiences.